Neurodevelopmental defects in a mouse model of O-GlcNAc transferase intellectual disability - Authier, Florence; Ondruskova, Nina; Ferenbach, Andrew T; McNeilly, Alison D; van Aalten, Daan M F (Disease models & mechanisms, 2024)
The addition of O-linked β-N-acetylglucosamine (O-GlcNAc) to proteins (referred to as O-GlcNAcylation) is a modification that is crucial for vertebrate development. O-GlcNAcylation is catalyzed by O-GlcNAc transferase (OGT) and reversed by O-GlcNAcase (OGA). Missense variants of OGT have recently been shown to segregate with an X-linked syndromic form of intellectual disability, OGT-linked congenital disorder of glycosylation (OGT-CDG). Although the existence of OGT-CDG suggests that O-GlcNAcylation is crucial for neurodevelopment and/or cognitive function, the underlying pathophysiologic mechanisms remain unknown. Here we report a mouse line that carries a catalytically impaired OGT-CDG variant. These mice show altered O-GlcNAc homeostasis with decreased global O-GlcNAcylation and reduced levels of OGT and OGA in the brain. Phenotypic characterization of the mice revealed lower body weight associated with reduced body fat mass, short stature and microcephaly. This mouse model will serve as an important tool to study genotype-phenotype correlations in OGT-CDG in vivo and for the development of possible treatment avenues for this disorder.
Keywords: mozek; N-Acetylglucosaminyltransferases; O-GlcNAcylation; N-acetylglukosaminyltransferasy; Phenotype; zvířata; myši; neurovývojové poruchy; mentální retardace; beta-N-Acetylhexosaminidases; Mice; beta-N-acetylhexosaminidasy; Vertebrate development; Intellectual Disability; glykosylace; Brain; fenotyp; Neurodevelopmental Disorders; Body Weight; Animals; Intellectual disability; tělesná hmotnost; Glycosylation; Disease Models, Animal; modely nemocí na zvířatech